2019
DOI: 10.1111/1462-2920.14602
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of theFusariumpathogens associated with crown rot in the Huanghuai wheat‐growing region of China

Abstract: Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 62 publications
(91 reference statements)
5
55
0
Order By: Relevance
“…The plant pathogen Fusarium pseudograminearum is the causative agent of Fusarium crown rot (FCR) in wheat and barley, resulting in substantial yield losses worldwide (Kazan and Gardiner 2018). Particularly, in the Huanghuai wheat-growing region of China, it has been reported that F. pseudograminearum was the dominant pathogen of FCR (Li et al 2012;Zhou et al 2019). F. pseudograminearum was initially recognized as a population within the Fusarium graminearum species group (group 1).…”
Section: Introductionmentioning
confidence: 99%
“…The plant pathogen Fusarium pseudograminearum is the causative agent of Fusarium crown rot (FCR) in wheat and barley, resulting in substantial yield losses worldwide (Kazan and Gardiner 2018). Particularly, in the Huanghuai wheat-growing region of China, it has been reported that F. pseudograminearum was the dominant pathogen of FCR (Li et al 2012;Zhou et al 2019). F. pseudograminearum was initially recognized as a population within the Fusarium graminearum species group (group 1).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat FCR caused by F. pseudograminearum has been spreading rapidly and has resulted in huge economic losses in the Huanghuai wheat-growing area of China since 2012 (Li et al 2012;Zhou et al 2019). However, only a few studies have evaluated the pathogenic mechanism of F. pseudograminearum.…”
Section: Discussionmentioning
confidence: 99%
“…The WT strain of F. pseudograminearum used for transformation and phenotypic analyses was Wz2-8A, which was isolated in Wuzhi, Henan Province of China (Zhou et al 2019). Both WT and genetically engineered strains in this study were cultured on potato dextrose agar (PDA) medium, containing 200 g/L potato, 20 g/L glucose and 20 g/L agar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously studies constructed a genetic map of F. pseudograminearum and completed a genomic sequence [9,10]. Zhou et al investigated the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat-growing region of China and found that F. pseudograminearum was the dominant species [11]. Several studies have con rmed that ER Lumenal Hsp70 protein FpLhs1, transcription factor FpAda1, and FpNPS9 are important for F. pseudograminearum infection [12][13][14].…”
Section: Introductionmentioning
confidence: 99%